2005
DOI: 10.1029/2004jc002385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tidal flat on the thermal effluent dispersion from a power plant

Abstract: [1] The effect of a tidal flat on the dispersion of thermal effluent from the nuclear power plant at YongGwang (5.8 Â 10 6 kW) along the west coast of Korea was investigated using intensive field observations and three-dimensional numerical simulations. The calculated sea surface temperature distribution reproduces well the observed one with a root mean square error of 0.53°C. A water column on the tidal flat area received a heat influx of 168 W m À2 on 17 April 2003 and transported the received heat to the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…This region is also where the role of heat transfer across the air-sea interface is expected to be greatest, due primarily to the large surface area of the far field plume [Fan and Brown, 2006;Yanagi et al, 2005].…”
Section: Conceptual View Of Plume Structure and Evolutionmentioning
confidence: 99%
“…This region is also where the role of heat transfer across the air-sea interface is expected to be greatest, due primarily to the large surface area of the far field plume [Fan and Brown, 2006;Yanagi et al, 2005].…”
Section: Conceptual View Of Plume Structure and Evolutionmentioning
confidence: 99%
“…The surface sediment temperature changes dramatically during the exposure of a tidal flat due to heat exchange with the atmosphere [Kim et al, 2007;Kim and Cho, 2009;Thomson, 2010]. The features of the seawater temperature variation in the tidal flat region are very complex due to heat exchange with the tidal flat and atmosphere [Choi et al, 2002;Yanagi et al, 2005]. The horizontal differences in the seawater temperature and seawater movement due to the tide cause spatial variability in the heat exchange between seawater and the bottom sediment in a coastal region.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a spectral analysis of the observed SST on the west coast of Korea showed semidiurnal variation due to heat exchange with the tidal flat [Choi et al, 2002]. Yanagi et al [2005] predicted the seawater temperature using the ocean numerical model, which considers the heat exchange between seawater and the tidal flat. Our previous study reported the effect of the tidal flat on the variability in the seawater temperature using the one-dimensional temperature prediction model on the western coast of Korea [Kim et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…According to their results, the occurrence of both strong coastal currents and winds during the winter and summer monsoons often results in a high rate of thermal dispersion. Yanagi et al (2005) took field observations for one month in spring 2003, under conditions of spring tides and fine weather, and performed 3d numerical modeling on the HNPP. Because of the limited data sampling, they found that the computed isotherm contours ran parallel to the coastline.…”
Section: Introductionmentioning
confidence: 99%